A heavy ion and proton radiation belt inside of Jupiter's rings. Issue 11 (3rd June 2017) - Kollmann, P.; Paranicas, C.; Clark, G.; Mauk, B. H.; Haggerty, D. K.; Rymer, A. M.; Santos‐Costa, D.; Connerney, J. E. P.; Allegrini, F.; Valek, P.; Kurth, W. S.; Gladstone, G. R.; et al.
Abstract: Energetic charged particle measurements by the Jupiter Energetic Particle Detector Instrument (JEDI) on board Juno have revealed a radiation belt of hundreds of keV ions up to the atomic mass of sulfur, located between Jupiter's rings and atmosphere. Proton energy spectra display an unusual intensity increase above 300 keV. We suggest that this is because charge exchange in Jupiter's neutral environment does not efficiently remove ions at such high energies. Since this innermost belt includes heavy ions, it cannot be exclusively supplied by cosmic ray albedo neutron decay, which is an important source at Earth and Saturn but only supplies protons and electrons. We find indications that the stripping of energetic neutral atoms in Jupiter's high atmosphere might be the ion source. Since the stripped off electrons are of low energy, this hypothesis is consistent with observations of the ratio of energetic electrons to ions being much less than 1. Plain Language Summary: Planets with their own a magnetic field, as Earth and Jupiter, are surrounded by "belts" of radiation. In case of Jupiter, most of this radiation extends to relatively large distances to Jupiter (several times the size of the planet) but is so strong that it is difficult to engineer satellites that can fly through them safely. Juno is the first spacecraft that repeatedly passes close to Jupiter and its Jupiter Energetic Particle Detector Instrument (JEDI) was now able to measure and quantify a small, separate radiation belt close to Jupiter. The measured population was unknown before and is located between Jupiter's atmosphere and its tenuous rings, inward to the main radiation belt. Key Points: There is a radiation belt within Jupiter's rings This innermost belt consists of ion masses up to sulfur but very few electrons Energetic neutral atoms may be the source of this innermost belt